2016
DOI: 10.15760/comminfolit.2016.10.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Do People Overestimate Their Information Literacy Skills? A Systematic Review of Empirical Evidence on the Dunning-Kruger Effect

Abstract: This systematic review has analyzed 53 English language studies that assessed and compared peoples' self-reported and demonstrated information literacy (IL) skills. The objective was to collect empirical evidence on the existence of Dunning-Kruger Effect in the area of information literacy. The findings clearly show that this theory works in this area. It is concluded that there is no calibration in peoples' perceived and actual IL skills; in most cases low-performers overestimate their skills in self-assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 40 publications
4
86
0
2
Order By: Relevance
“…Another possibllity is the existence of the Dunning-Kruger Effect, whereby people with low ability mistakenly assume greater ability through limited understanding (Kruger and Dunning, 1999). In support, Mahmood (2016) has previously reported the existence of the Dunning-Kruger effect in people's self-reported IL.…”
Section: Discussionmentioning
confidence: 89%
“…Another possibllity is the existence of the Dunning-Kruger Effect, whereby people with low ability mistakenly assume greater ability through limited understanding (Kruger and Dunning, 1999). In support, Mahmood (2016) has previously reported the existence of the Dunning-Kruger effect in people's self-reported IL.…”
Section: Discussionmentioning
confidence: 89%
“…(e.g. The Swedish Ministry of Education 2016) as well as with earlier research (Gross & Latham, 2012;Mahmood, 2016).…”
Section: Pupil's Perceptions Of Their Own Abilitiesmentioning
confidence: 83%
“…Additionally, previous research has shown that pupils often have a simple understanding of facts and tend to construct a dichotomy between facts and opinions (Alexandersson & Limberg, 2003). Furthermore, earlier research has consistently confirmed a relationship between low proficiency and overestimation of competence in relation to information literacy (Gross & Latham, 2012;Mahmood, 2016). Another starting point for research on IS and CAI in school settings in recent years has been the increasing significance of digital technology and the use of social media and search engines that has changed the information infrastructure of schools considerably (c.f.…”
Section: Research On Media and Information Literacy In School Settingsmentioning
confidence: 97%
“…3,12 Many studies deal with self-assessed student knowledge and skills in information searching [see, for example Kuhlthau,8 ] but there are few studies that investigate students' changing search strategies, particularly in higher education. Mahmood 25 demonstrates that students often overestimate their skills in information literacy, according to the Dunning-Kruger effect. 7…”
Section: Previous Researchmentioning
confidence: 99%